Diastolic dysfunction: from the discovery to the latest updates - T. V. Ashcheulova; H. V. Demydenko; N. M. Herasymchuk; Yu. K. Rezunenko; O. А. Kochubei; T. M. Ambrosova (Zaporožskij Medicinskij Žurnal)
Over a long period, chronic heart failure was primarily associated with impaired contractility of the left ventricular myocardium, which is a manifestation of systolic dysfunction. Based on modern ideas about the pathophysiology of CHF syndrome, systolic dysfunction is considered as one of the etiological factors along with changes in wall tension and the structure of diastolic filling, i.e. everything that is included in the concept of “LV remodeling”.